Edukasi Kesehatan Pada Masyarakat Desa Gampong Sungai Pauh Tanjung Tentang Budaya Perilaku Hidup Bersih dan Sehat - Muhammad Khairurrozi; Junius Mahara; Putri Mutia (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Applying PHBS (Clean and Healthy Living Behavior) should become a daily habit. It seems simple, but the reality is that many people are still unaware of the importance of PHBS to their health, their families, and the health of those around them. At home, PHBS  includes exclusive breastfeeding, delivery by a health care provider (midwife or doctor), scheduled immunizations, regular monitoring of infant and child growth and development, clinics, health centers, or child care. including Poyandu until she was 6 years old. Adopting a clean and healthy lifestyle (PHBS) for everyone is no easy task, but it is a long process. Everyone lives in their own order and influences and interacts with each other in this order. Monitoring, evaluating and measuring the progress of an order is easier than an individual. Developing a clean and healthy lifestyle (PHBS) therefore takes place through a methodical approach: the arrangement of homes, schools, public places, workplaces and health care facilities. PHBS in the Household is an attempt to make household members aware and willing to lead clean and healthy lives, and to play an active role in the wellness movement of their communities.